2013
DOI: 10.1166/jbn.2013.1713
|View full text |Cite
|
Sign up to set email alerts
|

Decreased 5-Hydroxymethylcytosine (5-hmC) is an Independent Poor Prognostic Factor in Gastric Cancer Patients

Abstract: DNA methylation at the 5 position of cytosine (5-mC) is a key epigenetic mark that is involved in various biological and pathological processes. 5-mC can be converted to 5-hydroxymethylcytosine (5-hmC) by the ten-eleven translocation (TET) family of DNA hydroxylases. Increasing evidence suggests that large-scale loss of 5-hmC is an epigenetic hallmark of several human cancers. However, the value of 5-hmC in diagnosis and prognosis of human cancers, including gastric cancer (GC), remains largely unknown. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 0 publications
4
47
1
Order By: Relevance
“…Very recently, Yang et al [12] reported that 5-hmC levels were markedly and negatively correlated with tumor invasion; that is, with the TNM stage and the number of lymph node metastases in GCs. They measured the 5-hmC level using a DNA dot blot assay and the down-regulation of TET1 transcripts was notably associated with a reduction of 5-hmC levels in GCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Yang et al [12] reported that 5-hmC levels were markedly and negatively correlated with tumor invasion; that is, with the TNM stage and the number of lymph node metastases in GCs. They measured the 5-hmC level using a DNA dot blot assay and the down-regulation of TET1 transcripts was notably associated with a reduction of 5-hmC levels in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Because dot blot analysis is based on the antigen-antibody reaction direct assessments of the absolute amount of 5-mC, 5-hmC, 5-fC, and 5-caC are not possible. Moreover, since the signal intensities of dot blot images become easily saturate, the standard curve used in the analyses is not linear [12]. In contrast to dot blot analysis, liquid chromatography coupled with tandem mass spectrometry (LC-MS/ MS) can calculate the absolute quantity of the modifications and its standard curve is completely linear.…”
Section: Introductionmentioning
confidence: 99%
“…This loss of 5hmC in genomic context may lead to gene body hypermethylation as observed in kidney cancer and can hypermethylate promoters of tumor suppressor genes (TSG) that are frequently observed in cancers [24]. Reduced 5hmC is a predictive marker for poor prognosis and survival for multiple cancers like breast, astrocytoma, laryngeal squamous cell carcinoma, renal, oesophageal, gastric and hepatocellular carcinoma (HCC) [24][25][26][27][28][29][30]. Moreover, mutations in TET2 are frequently observed with decrease in 5hmC in hematological cancers, additionally mutations of 5hmC regulating enzymes like IDH1/2, SDH and FH were also observed [19,20,31,32].…”
Section: Interplay Between 5-hydroxymethylcytosine and Cancermentioning
confidence: 99%
“…In recent years, 5-hmC has become more extensively studied. Previous studies have reported its position and prognostic value in a variety of tumors (17). However, the relationship between 5-hmC level and the progression of lung cancer and prognosis of patients with lung cancer remains unknown.…”
Section: Low Level Of 5-hmc Was Correlated With Poor Prognosis Of Nsclcmentioning
confidence: 99%